Trainer's manual on transformative leadership training for co-operatives transformative leadership, transformative co-operatives. - Asian Women in Cooperative Development Forum (Quezon City Asian Women in Cooperative Development Forum, 2001)
Facing the challenges of co-ops, an alternative future for co-ops and society. Teaching aids and materials. It is designed to increase the contribution of women in leadership and decision making in co-operatives and in other community-based organizations.
Keywords: Women in cooperative societies -- Asia -- Handbooks, manuals, etc; Leadership in women -- Asia -- Handbooks, manuals, etc